Sediment Delivery Ratio from a small Semiarid Watershed of Brazil - Piscoya, Victor Casimiro; de Melo, Robson Carlos Pereira; Cunha Filho, Moacyr; Guerra, Sergio Monthezuma Santoianni; Piscoya, Thaisa Oliveira Folha; Gomes Filho, Raimundo Raimundo Rodrigues; Fernandes, Milton Marques; Pedrotti, Alceu; Holanda, Francisco Sandro Rodrigues; de Araújo Filho, Renisson Neponuceno (Revista Brasileira de Geografia Física, 2021)
Assessing technologies based on sediment yield in watersheds is increasingly important to determine the delivery rate. This work aimed to determine values of sediment delivery of the hydrographic basin of the river Jacu in the semiarid of Pernambuco and its relations with the soil and vegetation. Therefore, it was calculated the rates of interrill and rill erosion by yield testing under shrub and uncovered Inceptisols conditions, and it was carried out direct measurement campaigns of suspended sediment and bedload, by means of US DH – 48 e US BLH – 84, respectively. The sediment yield obtained in Jacu stream was considered low. The soil loss due to interril erosion under uncovered conditions equal to 8.43 t ha-1 was considered high, as well as the same way for the values of rill erosion with erodibility equal to 0.0021142 kg N-1 s-1 and critical shear stress equal to 2.34 Pa. The mean value of sediment delivery ratio of Jacu watershed was equal to 0.165 and ranged from 0.29 in the year 2008 to 0.026 in 2010. This variation is associated with the natural variability of semiarid environment, indicating the necessity of assessment in a large period of years to improve the knowledge about the sediment delivery ratio of Jacu semiarid watershed. Taxa de entrega de Sedimentos de uma pequena bacia Semi-Árida do Brasil R E S U M O Avaliar tecnologias baseadas no rendimento de sedimentos em bacias hidrográficas é cada vez mais importante para determinar a taxa de entrega. Nesse trabalho objetivou-se determinar os valores de entrega de sedimentos da bacia hidrográfica do rio Jacu no semiárido de Pernambuco e suas relações com o solo e a vegetação. Portanto, foram calculadas as taxas de erosão entre perfurações e sulcos através de testes de rendimento sob condições arbustivas e descobertas de Inceptissolos, e foram realizadas campanhas de medição direta de sedimentos em suspensão e carga, por meio de US DH - 48 e US BLH - 84, respectivamente. O rendimento de sedimentos obtido no córrego Jacu foi considerado baixo. ...